Does the Presence of Circulating Tumor Cells in High-Risk Early Breast Cancer Patients Predict the Site of First Metastasis-Results from the Adjuvant SUCCESS A Trial - Trapp, Elisabeth K.; Fasching, Peter; Fehm, Tanja; Schneeweiss, Andreas; Mueller, Volkmar; Harbeck, Nadia; Lorenz, Ralf; Schumacher, Claudia; Heinrich, Georg; Schochter, Fabienne; De Gregorio, Amelie; Tzschaschel, Marie; et al. (Cancers, 2022)
Simple Summary Due to recent advances in breast cancer detection and treatment strategies, the number of breast cancer survivors has increased over the past decades. However, breast cancer follow-up guidelines have not changed for years. The presence of CTCs detected during follow-up has been shown to indicate poor prognosis in high-risk breast cancer patients. Here, we evaluated if the presence of CTCs also indicates the site of metastatic disease by analyzing CTC status and metastatic location in 206 patients with distant recurrence from the large adjuvant breast cancer trial SUCCESS A. Patients who were CTC-positive both before and after chemotherapy were more likely to show bone-only first distant disease (37.5% vs. 21.0%) and first distant disease at multiple sites (31.3% vs. 12.6%) than patients without CTCs. These data indicate that CTCs might serve as a liquid biopsy surveillance-marker enabling risk-stratification for deciding on further adjuvant add-on-treatment. The prognostic relevance of circulating tumor cells (CTCs) in breast cancer is well established. However, little is known about the association of CTCs and site of first metastasis. In the SUCCESS A trial, 373 out of 3754 randomized high-risk breast cancer patients developed metastatic disease. CTC status was assessed by the FDA-approved CellSearch(R)-System (Menarini Silicon Biosystems, Bologna, Italy) in 206 of these patients before chemotherapy and additionally in 159 patients after chemotherapy. CTCs were detected in 70 (34.0%) of 206 patients before (median 2 CTCs, 1-827) and in 44 (27.7%) of 159 patients after chemotherapy (median 1 CTC, 1-124); 16 (10.1%) of 159 patients were CTC-positive at both timepoints. The site of first distant disease was bone-only, visceral-only, and other-site-only in 44 (21.4%), 60 (29.1%), and 74 (35.9%) patients, respectively, while 28 (13.6%) patients had multiple sites of first metastatic disease. Patients with CTCs at both timepoints more often showed bone-only first distant disease (37.5% vs. 21.0%) and first distant disease at multiple sites (31.3% vs. 12.6%) than patients without CTCs before and/or after chemotherapy (p = 0.027). In conclusion, the presence of CTCs before and after chemotherapy is associated with multiple-site or bone-only first-distant disease and may trigger intensified follow-up and perhaps further treatment.
CRIS-Team WoS Importer:2022-09-09